2022
DOI: 10.1063/5.0103642
|View full text |Cite
|
Sign up to set email alerts
|

Atomically precise binding conformations of adenine and its variants on gold using single molecule conductance signatures

Abstract: We demonstrate single molecule conductance as a sensitive and atomically precise probe of binding configurations of adenine and its biologically relevant variants on gold. By combining experimental measurements and density functional theory (DFT) calculations of single molecule–metal junction structures in aqueous conditions, we determine for the first time that robust binding of adenine occurs in neutral or basic pH when the molecule is deprotonated at the imidazole moiety. The molecule binds through the dona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In addition, we observe that BI only forms junctions in conditions whose pH is above the pKa of BI (∼5), as has also been previously reported for Im. ,, This result indicates that deprotonation of the BI at the nitrogen linkers is required for junction formation. The similarity of pH-dependent conductance signatures for BI and Im establishes that the same binding mechanism is responsible for the HG peaks of both molecules.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In addition, we observe that BI only forms junctions in conditions whose pH is above the pKa of BI (∼5), as has also been previously reported for Im. ,, This result indicates that deprotonation of the BI at the nitrogen linkers is required for junction formation. The similarity of pH-dependent conductance signatures for BI and Im establishes that the same binding mechanism is responsible for the HG peaks of both molecules.…”
supporting
confidence: 88%
“…An alternative approach is to design molecular components that can rearrange and self-assemble into novel molecular structures in the junction. For example, imidazole (Im)a conjugated five-member heterocyclecan become deprotonated to imidazolate in the junction environment and then bridge gold electrodes to form Im–gold bridges. , Other work shows that intermolecular interactions can be harnessed to create new junction structures. For example, researchers have synthetically manipulated π–π coupling between oligo­(phenylene–ethynylene) (OPE) molecules to achieve junctions with through-space transport, quantum interference, and environmental controls . Additionally, other conjugated molecules containing multiple π–π stacked units were observed to demonstrate a significant increase in conductance due to constructive quantum interference. , …”
mentioning
confidence: 99%
“…We use a home-built STMBJ setup as previously described. ,, All molecules are dissolved in water to a concentration of ∼5 mM, and the solution pH is adjusted as needed through addition of sodium hydroxide, NaOH (see the Supporting Information for more details). As detailed in the Supporting Information and prior work, we deposit molecules onto the gold-coated substrate using the dip-coating method onto the gold-coated substrate. , A gold tip is repeatedly brought in and out of contact with the gold-molecule-coated substrate to record molecular conductance. At each cycle, the molecule of interest can bridge the interelectrode gap.…”
mentioning
confidence: 99%
“…6,7 We and others have shown that single-molecule conductance measurements can be used to determine the binding conformation of biological molecules, such as adenine, on gold surfaces. 24 Adenine, like histidine, contains a five-membered heterocyclic imidazole ring containing two nitrogen atoms. We found that the imidazole ring can bridge between two gold electrodes in basic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation